Forward Left Ventricular Ejection Fraction: A Simple Risk Marker in Patients With Primary Mitral Regurgitation. Issue 11 (27th October 2017) - Dupuis, Marlène; Mahjoub, Haïfa; Clavel, Marie‐Annick; Côté, Nancy; Toubal, Oumhani; Tastet, Lionel; Dumesnil, Jean G.; O'Connor, Kim; Dahou, Abdellaziz; Thébault, Christophe; Bélanger, Catherine; Beaudoin, Jonathan; et al.
Abstract : Background: The timing of mitral valve surgery in asymptomatic patients with primary mitral regurgitation (MR) is controversial. We hypothesized that the forward left ventricular (LV) ejection fraction (LVEF; ie, LV outflow tract stroke volume divided by LV end‐diastolic volume) is superior to the total LVEF to predict outcomes in MR. The objective of this study was to examine the association between echocardiographic parameters of MR severity and LV function and outcomes in patients with MR. Methods and Results: The clinical and Doppler‐echocardiographic data of 278 patients with ≥mild MR and no class I indication of mitral valve surgery at baseline were retrospectively analyzed. The primary study end point was the composite of mitral valve surgery or death. During a mean follow‐up of 5.4±3.2 years, there were 147 (53%) events: 96 (35%) MV surgeries and 66 (24%) deaths. Total LVEF and global longitudinal strain were not associated with the occurrence of events, whereas forward LVEF ( P <0.0001) and LV end‐systolic diameter ( P =0.0003) were. After adjustment for age, sex, MR severity, Charlson probability, coronary artery disease, and atrial fibrillation, forward LVEF remained independently associated with the occurrence of events (adjusted hazard ratio: 1.09, [95% confidence interval]: 1.02–1.17 per 5% decrease; P =0.01), whereas LV end‐systolic diameter was not ( P =0.48). Conclusions: The results of this study suggest that the forward LVEF may be superior to the total LVEF and LV end‐systolic diameter to predict outcomes in patients with primary MR. This simple and easily measurable parameter may be useful to improve risk stratification and select the best timing for intervention in patients with primary MR.